Real-word evaluation of differences in bowel preparation for colonoscopy between the digestive and the non-digestive physicians: A retrospective study - Liu, Cenqin; Yuan, Xin; Gao, Hui; Zhang, Zhixin; Wang, Weihong; Xie, Jiarong; Lu, Hongpeng; Chen, Jian; Yu, Chaohui; Xu, Lei (Frontiers in Gastroenterology, 2022)
Abstract Introduction: Using real-world data, we compared the quality of bowel preparation instructed by the digestive and non-digestive physicians in outpatients for colonoscopy, and identified potential risk factors. Methods: This was a retrospective study based on real-world data, which was collected from the Ningbo First Hospital in China from December 2019 to October 2020. Outpatients included were classified into the digestive and the non-digestive physician groups according to the referring physician. The primary outcome was adequate bowel preparation measured by the Boston Bowel Preparation Scale (BBPS), namely, a BBPS score of 2 or higher in any colonic segment and a total score ≥ 6. Secondary outcomes included the total mean BBPS scores and possible risk factors associated with poor bowel preparation. Results: There were 671 outpatients included, with 392 in the digestive physician group and 279 in the non-digestive physician group. Adequate bowel preparation was 84.2% in the digestive physician group and 71.0% in the non-digestive physician group (odds ratio [OR] 1.50, p < 0.001), and the latter had lower total mean BBPS scores (6.12  1.33 vs 6.661.29, p < 0.001). The non-digestive physician was an independent risk factor according to the multivariate logistic regression analysis (OR 0.45, p < 0.001). Conclusion: The quality of bowel preparations instructed by non-digestive physicians was inferior to digestive physicians, which was a factor potentially associated with poor bowel preparation (ClinicalTrials.gov number: NCT04738578).